Effect of Workload, Job Stress and Job Training on Employee Performance at Bank BPR BKK Semarang - Aulia Choirunnisa; Heri Prabowo; M.Fadjar Darmaputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted with the aim of knowing the effect of workload, work stress and job training on the performance of Bank BPR BKK Semarang employees. This research uses multiple linear regression analysis method with statistical test tools. The measurements in this study used a Likert scale and then processed the data in this study using the IBM SPSS 25 tool. The results of the study show that the workload variable has a negative and significant effect on employee performance. Work stress variable has a negative and significant effect on employee performance. Meanwhile, the job training variable has a positive and significant effect on employee performance.